2013
DOI: 10.5935/abc.20130167
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism G894T and the Prognosis of Heart Failure Outpatients

Abstract: BackgroundPrevious studies have analyzed the role of the genetic polymorphism of endothelial nitric oxide synthase on heart failure prognosis. However, there are no studies relating the G894T and heart failure in Brazil. ObjectiveTo evaluate the association between G894T GP and the prognosis of a sample of Brazilian outpatients with heart failure. MethodsCohort study included 145 patients with systolic heart failure, followed for up to 40 months (mean = 22), at two university hospitals, in the State of Rio de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…For instance Velloso et al studied a multi-ethnic Brazilian population and demonstrated increased frequency of GG genotype in patients with systolic heart failure compared with healthy controls [ 7 ]. Another Brazilian study showed GG genotype was associated with a near 5% reduction in LVEF compared with TT genotype patients, findings very similar to those of the current study [ 18 ]. Also noteworthy is the higher all-cause mortality associated with the GG genotype in hypertensive patients [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…For instance Velloso et al studied a multi-ethnic Brazilian population and demonstrated increased frequency of GG genotype in patients with systolic heart failure compared with healthy controls [ 7 ]. Another Brazilian study showed GG genotype was associated with a near 5% reduction in LVEF compared with TT genotype patients, findings very similar to those of the current study [ 18 ]. Also noteworthy is the higher all-cause mortality associated with the GG genotype in hypertensive patients [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…G894T carriers show less NO production and it may be a factor that increases patients' susceptibility to atherosclerotic disease. The frequency of the mutant allele was more frequent in the Brazilian [62], Mexican [63] and Italian [64] populations. The wild type allele is more frequent in England [54], Germany [65], Turkey [66], South Africa [67] and in the African-American population [68].…”
Section: Endothelial Nitric Oxide Synthasementioning
confidence: 99%